The Equivalence in The Translation of English Idiomatic Expression into Indonesian by Students of English Education Department University of Mataram - Nilam Sari; Arifuddin Arifuddin; Baharuddin Baharuddin (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
The aims of this study are: 1) to find out frequently used types of equivalence by the seventh semester students of English Education Department at University of Mataram  in translating English idiomatic expression into Indonesia according to Nida’s equivalence theory, and 2) to find out the problem faced by the English students in the translating of the idiomatic expression of English into Indonesia. This study used mixed-method. The participant of this study were from the seventh semester English students of University of Mataram. To collect the data, this study used two types of instruments: translation test and questionnaires. The research findings showed that among 240 datas of students translation result, 73,64% of the datas categorized as dynamic equivalence and only 5,85% of the datas categorized as formal equivalence. Furthermore, based on close-ended and open-ended questionnaires answers about students dificulty in the translating of the idiomatic expressions, it reveals that students faced difficulty in translating process for the cultural background diferences, minim exposure to idioms, and how the idioms were used. three strategies were available to students to use in encountering the difficulties in translating English idioms into Indonesian: 1) giving their selves more familiar to idioms through reading and using various medias, 2) paying more attention to the context which the idioms being served, 3) and looking for the meaning in dictionary or google. It could be infered that the most frequently used types of equivalence by the students was dynamic equivalence and the students still faced some problem in translating English idiomatic expression into Indonesia.Keywords: idiomatic expression; translation equivalence; difficulties